The Tipulidae (Diptera) of Slovenia, Croatia, Bosnia and Herzegovina, Serbia, Monte Negro, and Macedonia - Simova-Tošić, Duška (Acta entomologica slovenica (Ljubljana), 2003)
155 species of the family Tipulidae (Diptera), known from the countries that in the recent past formed Yugoslavia, are listed. Five species are new for theregion: Nephrotoma appendiculata pertenua Oosterbroek, Tipula (Pt.) cinereicosta Lundstrom, T. (S.) boreosignata Tjeder, T. (S.) cheethami Edwardsand T. (T.) italica italica Lackschewitz. The numbers of taxa by country are: Slovenia 82, Croatia 86, Bosnia and Herzegovina 75, Serbia 92, Monte Negro 75, and Macedonia 97. 11 species which, by present knowledge, do not occur in the area, are omitted from the list.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; Croatia; Črna gora; dvokrilci; entomologija; Hrvaška; Makedonija; Republic of Macedonia; Serbia; Slovenia; Slovenija; Srbija